TINGKAT KESESUAIAN PANTAI NGURSARNADAN KABUPATEN MALUKU TENGGARA TERHADAP AKTIVITAS REKREASI PANTAI - Renjaan, Melissa; Renjaan, Eugenius Alfred (JURNAL LEMURU, 2022)
Tourism in coastal and marine areas is still an attraction in the eastern Indonesian archipelago. One of the famous beaches as a favorite tourist destination is Ngursarnadan Beach in Southeast Maluku Regency. White sand beaches, clear waters, lagoons, and coral reef areas are its various potential. Seeing the high number of tourist visits to Ngursarnadan Beach, it is necessary to study the suitability of tourism on Ngursarnadan beach as a step to optimally sustainable use of coastal and marine areas. Knowing the suitability of Ngursanadan beach for tourism activities is the aim of this study. Furthermore, the method used is the quantitative method with Analysis of the Tourism Suitability Index. The suitability of tourism at station 1 has a higher value than the standard value of 2.5, which is 2.83. This value is included in the very suitable category for beach recreation. Furthermore, at station 2, the suitability value is 2.75 > 2.5, indicating that station 2 is very suitable for beach tourism activities. The very suitable category is also shown at station 3 with a value of 2.75 > 2.5. Based on the results of the study, it was concluded that the Ngursarnadan Ohoililir beaches are very suitable for beach tourism activities.